- #1

oneamp

- 219

- 0

## Homework Statement

Find the general solution:

y'' - y' - 2y = -2t + 4t^2

## Homework Equations

## The Attempt at a Solution

r_1 = 2, r_2 = (-1)

Set Y(t) = At^2 + B^t + C

Y' = 2At + B

Y'' = 2A

2A - 2At + B - 2At^2 + Bt + C = -2t + 4t^2

-2At^2 + (B-2A)t + 2A + B + C = -2t + 4t^2

-2A = 4

B - 2A = (-2)

2A + B + C = 0

The solution should have -2 = A, 3 = B, and -7/2 = C.

But when I solve it, given the equations above, I don't get that. I only have A right.

What's wrong?

Thank you